TINGKAT FILTRASI RUMPUT LAUT (GRACILARIA SP) TERHADAP KANDUNGAN ORTOFOSFAT (P2O5) - Wage Komarawidjaja (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
The Concern of this study is to understand Gracilaria sp. function in biofiltration process as a way in removing exceeding nutrient.Laboratory analysis indicated that Gracilaria sp has the ability to reduce organic substance as orthophosphate in see water up to range 0.0082 -00.0149 ppm/days. Application of Gracilaria in waste water filtrattion is expected to be an alternative approach in shrimp pond waste water treatment.